The Negative effects on the immune system of native chicken embryos (Gallus gallus domesticus) due to extreme environmental fluctuations before incubation - lelono, Asmoro (Life Science and Biotechnology, 2025)
Climate variability can influence avian reproductive success by altering environmental factors critical to egg viability and embryonic development. In avian species such as Gallus gallus domesticus, the period before incubation exposes eggs to fluctuating conditions that may affect their survival and the offspring’s physiological performance. This study evaluated the effects of pre-incubation environmental conditions on the growth and immune response of native chickens. Fertilized eggs were subjected to different temperature and humidity treatments before incubation to simulate natural ecological variations. The findings revealed that neither low-temperature exposure nor excessive moisture significantly reduced egg viability or embryonic development. Post-hatching observations, including biometric parameters and tonic immobility tests, showed no significant behavioral differences among treatment groups. Although all chicks exhibited daily weight gain, those from the control group displayed more stable growth patterns, indicated by lower standard error values. Measurements of innate immune response, inferred from body temperature fluctuation, were comparable across groups. These results suggest that native chicken eggs possess physiological plasticity that enables them to maintain normal embryogenesis and immune development under variable environmental conditions